Consequences of School Mobility on Teachers' Labor Welfare: a case study in a Rural School in the V Region of Chile - Amanda Contreras; Bastián Urrutia; Yanara Figueroa (Revista Brasileira de Educação do Campo)
In Chile, during the 2010s a remarkable phenomenon of school mobility from urban schools to rural schools was observed due to exclusion practices, generating a significant impact on the enrollment of the latter in terms of composition. The main objective of this research is to analyze the consequences that school mobility can have on teachers' labor welfare in rural schools. To achieve this, a qualitative methodology was employed through an intrinsic case study, using techniques such as semi-structured individual interviews and a focus group with 5 teachers from a rural school in the V region. The main results indicate that school mobility has implications for teachers' labor welfare, since teachers must face the extra challenges posed by diversity in the classroom as a result of the arrival of students with special educational needs. Although these challenges may represent risk factors for the occupational well-being of educators, the latter resignify these problems as a function of wanting to heal these students with previous experiences of school exclusion.